Pendekatan Design For Six Sigma Pada Perancangan Sistem Informasi Preventive Maintenance Untuk Support Facilities Perangkat BTS (Base Transceiver Station) - Taufiqurrahman, Muhammad (Faculty of Engineering, Universitas Tanjungpura, 2015)
Abstract– Management of data and information about maintenance is an important factor in supporting the preventive maintenance of support facilities BTS device. There are difficulties to gathering information and processing data related to preventive maintenance, because the system using filing and archiving with the use of paper as a medium. Design for six sigma approach performed as a method to determine user needs and accommodate these needs into the information system of preventive maintenance as a solution arising from the system of filing and archiving. The development of information technology allows for the development of information systems to support preventive maintenance. The results showed with the implementation of preventive maintenance information system, occurs an increase will ease the management of data and information in support of preventive maintenance support device BTS facilities. This is indicated by the user's perception associated with filing and archiving system preventive maintenance which was originally 53.3% using paper documents to 84.4% after using a system of preventive maintenance information. Keywords– Preventive Maintenance, Information System, Design For Six Sigma (DFSS), support facilities BTS Device